RANCANG BANGUN MESIN PEN GADUK DODOL KAPASITAS 5 KG - Prabowo , Sandy; Monica Syalfha; Sugianto; Idiar (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Bangka’s typical dodol has a sweet taste, and a soft texture and food that isrelatively durable. The typical Bangka dodol ingredients used are coconut milk,granulated sugar, palm sugar, and sticky rice. The results of observations withUMKM PAHLAWAN IV in Nibung village, dodol artisans still use human labor asa source of motivation. From these problems, the idea of designing and making adodol stirring machine emerged which aims to assist PAHLAWAN IV UMKM inthe process of stirring dodol from a manual system to a mechanical system. Themethod used in making this machine uses the VDI 2222 method. This method has 4(four)stages,namelyanalysis,conceptualization,designing,andcompletion.Fromthis stage of conceptualizing, alternative part functions are produced. Alternativepart functions are then given an assessment to determine alternative part functionsusedinmachinemanufacturing.Furthermore,thealternativefunctionoftheselected part will be optimized for design. The dodol stirring machine made hasspecifications of 650 mm in length, 650 mm in width, and 900 mm in height. Thedrivesourceusesa 1/2HPelectric motor with1,400rpm.Thetransmissionsystemuses a 1:50 size 60 gearbox which is passed on by pulleys and V-Belts. Based onthe results of the trial, the results of the 5kg capacity dough were obtained in 1(one)process with a period of 4 to 8 hours.